2010
DOI: 10.5194/hess-14-505-2010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of soil moisture feedback to hydroclimatic variability

Abstract: Abstract. While a variety of model experiments and analyses of observations have explored the impact of soil moisture variation on climate, it is not yet clear how large or detectable soil moisture feedback is across spatial and temporal scales. Here, we study the impact of dynamic versus climatological soil moisture in the GISS GCM ModelE (with prescribed sea-surface temperatures) on the variance and on the spatial and temporal correlation scale of hydrologically relevant climate variables (evaporation, preci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
(60 reference statements)
3
23
0
Order By: Relevance
“…The importance of the nonlinear atmosphere response to periodic terms must be emphasized. Krakauer et al (2010) indicated that P variance has a nonlinear response to the combined interannual variability of sea surface temperature and SM. Stuecker et al (2013) used observational and climate model data to highlight the importance of the nonlinear atmospheric response to the annual cycle of sea surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the nonlinear atmosphere response to periodic terms must be emphasized. Krakauer et al (2010) indicated that P variance has a nonlinear response to the combined interannual variability of sea surface temperature and SM. Stuecker et al (2013) used observational and climate model data to highlight the importance of the nonlinear atmospheric response to the annual cycle of sea surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic land cover and land use change (LCLUC) affects climate by modifying water, sensible heat, and radiation fluxes at the land surface (Chase et al, 2000;Gordon et al, 2005;Brovkin et al, 2006;Findell et al, 2007;Krakauer et al, 2010;Mahmood et al, 2014). One important mode of LCLUC has been the dramatic expansion in irrigated agriculture over the past century.…”
Section: Introductionmentioning
confidence: 99%
“…864 N. Y. Krakauer et al: Air-sea coupling and irrigation Many GCM studies of irrigation's climate impacts have been conducted with prescribed sea surface temperatures (SSTs) (Boucher et al, 2004;Puma and Cook, 2010;de Vrese et al, 2016), while several did include ocean-atmosphere interaction (Lobell et al, 2006;Cook et al, 2011Cook et al, , 2015. Various studies have highlighted the importance of interactive atmosphere-ocean coupling for accurately reproducing various phenomena in GCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous statistical and model assessments of East Asian or global land‐atmosphere coupling mainly focused on the timescales from days to months [e.g., Koster et al , 2004; Kim and Hong , 2007; Chow et al , 2008; Zhang et al , 2008b; Dirmeyer et al , 2009]. Several previous studies have used AGCM simulations to investigate the contribution of soil moisture feedbacks to interannual climate variability on the global scale [e.g., Koster et al , 2000; Reale and Dirmeyer , 2002; Krakauer et al , 2010]. However, as mentioned above, AGCM studies of land‐atmosphere coupling have large uncertainties on the local to regional scales.…”
Section: Introductionmentioning
confidence: 99%